Text-matching software in post-secondary contexts: A systematic review protocol - Hayden, Alix; Eaton, Sarah Elaine; Crossman, Katherine; Penaluna, Lee-Ann; Lenart, Bartlomiej A. (Canadian Perspectives on Academic Integrity, 2020)
This protocol outlines the methods for our systematic review on commercial text-matching software (TMS). We propose to use Joanna Briggs Institute’s (JBI) Methodology for Mixed Methods Systematic Reviews. This systematic review will provide insights into how TMS is used in post-secondary contexts, highlighting evidence relating to how well such software reduces incidences of plagiarism, and also how it can be used for educational purposes to support student learning at the undergraduate and graduate levels.